Penerapan Good Corporate Governance Pada Kinerja Perusahaan Sektor Keuangan Dengan Manajemen Resiko - Arfi Andira Kirana; Muhammad Irwan Padli Nasution (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2023)
The objective of this research is to analyze the impact of implementing Good Corporate Governance (GCG) on risk management and the performance of financial sector companies listed on the Indonesia Stock Exchange (IDX). The implementation of GCG is assessed through the Corporate Governance Perception Index (CGPI). Effective GCG is an innovative instrument that promotes efficient management. This concept emphasizes the importance of companies' obligation to provide relevant, accurate, and transparent disclosures regarding their operations, ownership, stakeholders, and shareholders' rights to access timely and reliable information. This research adopts a qualitative methodology with a literature review approach. Based on the research findings, companies can successfully implement good corporate governance if they can overcome the challenges they face.